Psychophysiological effects of different execution speeds of single bout exercise in outdoor fitness equipment performed by older men - Welmo Alcântara Barbosa; Roberta Luksevicius Rica; Francisco Luciano Pontes Junior; Victor Machado Reis; Marco Bergamin; Danilo Sales Bocalini (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aims: This study aimed to investigate the effects of different cadences of movement in ATI equipment on the psychophysiological parameters of older adults during the training session. Methods: Fifteen physically independent older men voluntarily participated in this study. Three 30-min exercise sessions were randomly distributed (5 min warm-up, 20 min exercise, 5 min cooldown), comprising exercises with different cadences low (L: 1 movement every 4 s), medium (M: 1 movement every 2 s), and high cadence (H: 1 movement per second); all with 30" of stimulus and 30" recovery using the following devices: elliptical, rower, surf/elliptical and leg press. Heart rate (HR), rate of perceived exertion (RPE), rate of perceived recovery (RPR), and feeling scale (FS) were evaluated before and immediately after the three sessions. The difference between moments was analyzed by analysis of variance with a significance level of p < 0.0001). Results: Cadence L (56 ± 2 %) showed lower values of relative HR than M (70 ± 5%) and H (85 ± 5%), which also differed from each other. Significant differences (p < 0.01) for the area under the curve of RPE (L: 75 ± 26, M: 115 ± 16, H: 154 ± 4) and RPR (L: 173 ± 16, M: 139 ± 12, H: 97 ± 6; UA) were identified among the cadences. Statistical differences (p < 0.01) were found on RPE 30 min of the session (L: 4.2 ± 0.7 < M: 5.7 ± 0.7 < H: 7.4 ± 0.5). Conclusion: The performance of different cadences induced different psychophysiological responses in older adults undergoing exercise sessions in the ATI. The moderate cadence provided an increase in HR with values considered safe for the exercise and therefore can be recommended for this population when using this equipment.